2015
DOI: 10.1016/j.plaphy.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Potassium phosphite increases tolerance to UV-B in potato

Abstract: The use of biocompatible chemical compounds that enhance plant disease resistance through Induced Resistance (IR) is an innovative strategy to improve the yield and quality of crops. Phosphites (Phi), inorganic salts of phosphorous acid, are environment friendly, and have been described to induce disease control. Phi, similar to other plant inductors, are thought to be effective against different types of biotic and abiotic stress, and it is assumed that the underlying signaling pathways probably overlap and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 47 publications
1
32
0
3
Order By: Relevance
“…Los fosfitos, como alternativa para el control de organismos fitoparásitos, han sido estudiados ampliamente y su eficacia se ha probado contra protozoarios, oomycetes, hongos, bacterias y nematodos fitoparásitos (Cuadro 1); adicionalmente, se ha comprobado su eficacia como bioestimulador (Gómez-Merino y Trejo-Téllez, 2015), para disminuir los daños por malezas (Manna et al, 2016;Achary et al, 2017) y radiación UV-B (Oyarburo et al, 2015).…”
Section: Application Methodsunclassified
See 1 more Smart Citation
“…Los fosfitos, como alternativa para el control de organismos fitoparásitos, han sido estudiados ampliamente y su eficacia se ha probado contra protozoarios, oomycetes, hongos, bacterias y nematodos fitoparásitos (Cuadro 1); adicionalmente, se ha comprobado su eficacia como bioestimulador (Gómez-Merino y Trejo-Téllez, 2015), para disminuir los daños por malezas (Manna et al, 2016;Achary et al, 2017) y radiación UV-B (Oyarburo et al, 2015).…”
Section: Application Methodsunclassified
“…However, 40 years later, phosphites returned to the agrochemicals market as an alternative for controlling plant diseases, when the French company Rhône-Poulenc offered the active ingredient fosetyl-aluminum to control mildews and diseases caused the Phytophthora genus (Tkaczyk et al, 2016;Achary et al, 2017). Phosphites, as an alternative for controlling phytoparasite organisms, have been extensively studied and proven to be effective against protozoa, oomycetes, fungi, bacteria and phytoparasite nematodes (Table 1), as well as biostimulators (Gómez-Merino and TrejoTéllez, 2015) that reduce damages caused by weeds (Manna et al, 2016;Achary et al, 2017) and UV-B radiation (Oyarburo et al, 2015).…”
Section: Fully Bilingual Revista Mexicana De Fitopatologíamentioning
confidence: 99%
“…Bishwoyog and Swarnima (2016) reviewed that a yield of 30 tons of potato tubers will removes 250 kg of potassium per hector. It has been established in several previous studies that addition of potassium at adequate level, which depends on soil fertility, crop rotation and soil type, improves tuber yield attributes (Zelelew et al, 2016;Haddad et al, 2016), tuber quality attributes (Abd El-Latif et al, 2011;Michalska et al, 2016), plant tolerance to biotic and abiotic stresses (Abd El-Latif et al, 2011;Oyarburo et al, 2015;Liljeroth et al, 2016).…”
Section: Accordingmentioning
confidence: 99%
“…Interestingly, Estrada-Ortiz et al (2013) showed that adding Phi to the nutrient solution used for growing strawberries improves some fruit quality characteristics when there is sufficient Pi, and it has been postulated that Phi could activate defense mechanisms against pathogen attack. In fact, Oyarburo et al (2015) recommend the use of Phi as an agent to activate defense, cellular signal transduction and quality improvement mechanisms in certain conditions and for certain crops. The only way that plants can use Phi as a P-source is through the expression of a bacterial phosphite dehydrogenase, as has been reported for Arabidopsis thaliana and Nicotiana tabacum (López-Arredondo and Herrera-Estrella 2012), which opens up new opportunities to use Phi as a P-source in P nutrition approaches.…”
Section: Phosphorus (P)mentioning
confidence: 99%